Investing in economic inclusion and resilience: Impacts of Kenya’s Economic Inclusion Programme - Endline results for cohort 2 - Hidrobo, Melissa; Abay, Kibrom A.; Ayalew, Hailemariam; Gilligan, Daniel O.; Kimathi, Sally; Kosec, Katrina; Zafar, Sarim (CGIAR System Organization, 2025)
This project note presents endline findings from the impact evaluation of Kenya’s Economic Inclusion Programme (EIP) Cohort II, using a cluster randomized controlled trial. The EIP combined consumption support, productive asset transfers, skills training, mentorship, and village savings and loans association (VSLA) participation to strengthen the economic resilience of extreme poor households. Results show substantial improvements in household welfare: total consumption rose by 19 percent, food insecurity fell by 9 percentage points, and minimum dietary diversity among women improved by 19 percentage points. The programme also stimulated economic activity, increasing farm and non-farm incomes, facilitating business creation and expansion, and financial inclusion—particularly savings and borrowing through VSLAs. Short-term impacts on asset accumulation were modest, and no significant effects were found on mental health or women’s decision-making, though trust in local leaders, NGOs, and banks improved, alongside some gains in gender equitable attitudes. Overall, EIP effectively addressed multiple constraints facing poor households and supported their social and economic inclusion.